Evaluation of Management of Logistic Materials Management Practice as a Dental Technician Health Service Officer 2018 - Febria Listina; Satria Nandar Baharza; Reka Aprilia (GLOBAL HEALTH SCIENCE GROUP, 2022)
Dental Engineering Department has a very big role for the creation of competent graduates. In carrying out its role, the Dental Engineering Department must be able to manage education properly and correctly, one of them is logistical management of practicum materials. The purpose of this study was to find out in depth about the evaluation of logistics management in the form of input, process, output of the management of practicum materials at the Department of Dental Engineering, Poltekkes Tanjung Karang. The logistics management function of practicum materials includes identifying, planning procurement, distributing tools to developing an effective and efficient logistics management system.The method used in this study is qualitative with 9 informants. The place of research was carried out in the dental engineering department of Health Polytechnic Tanjung Karang. Data collection is done by direct interviews and observations.The results of this study in general the management of logistics in the Department of Dental Engineering Health Polytechnic Tanjung Karang is quite good but there are still some obstacles such as inadequate Human Resources, inconsistent procedures implemented, nonstandard storage facilities and the planning process of practicum material requirements that have not used the method raw.Therefore, an additional employee in the support unit is needed, repairs to the warehouse and using a standard method, the Activity Based Casting (ABC) method.